Crafting the multiferroic BiFeO3-CoFe2O4 nanocomposite for next-generation devices: A review. Issue 14 (26th October 2021) - Amrillah, Tahta; Hermawan, Angga; Wulandari, Chandrawati Putri; Muthi'Ah, Aisyah Dewi; Simanjuntak, Firman Mangasa
ABSTRACT: BiFeO3 -CoFe2 O4 (BFO-CFO) vertically aligned nanocomposite (VAN) thin-film promises great potentials for next-generation electronic devices. Its strong magnetoelectric, antiferromagnetic-ferrimagnetic, and structural couplings occur via large interface area interactions across the vertical surface between BFO and CFO phases; this leads to emergent exotic fundamental physics rendering its potential applications for various electronics, such as magnetic sensor, data storages or memory devices, and energy harvesting devices. The distinctive photoactivity of both BFO and CFO phases in the BFO-CFO VAN system also can generate advanced applications as photovoltaic and photocatalytic devices. Furthermore, owing to small overpotential and excellent stability in alkaline media, BFO-CFO nanocomposites becomes the next electrode in electrocatalysis devices. The BFO-CFO VAN also have been exponentially developed having various type of thin-film architectures grown on various substrates. In this present article, we review the current status of the BFO-CFO VAN thin-film and discuss the fundamental understanding as well as the technology involved in developing this material. We also address the challenges that hinder the commercialization of this material and propose some plausible solutions to encourage BFO-CFO VAN-based electronic devices to reach their maturity level. Furthermore, the potential marketability of the BFO-CFO VAN materials and devices for future consumer products is also discussed.